Novel platinum II and platinum IV complexes exhibit potent cytotoxicity and selectivity towards several cancer cell lines - Elias, Elias (2020)
The discovery of cisplatin and its antineoplastic potential directed research toward the usage of platinum-based complexes as chemotherapeutical drugs. The aim of the present study is to test the anticancer activity of two novel platinum complexes Pt(II) and Pt(IV) on lung cancer cells (A549), breast cancer cells (MDA-MB-231), melanoma cells (A375), and mesenchymal stem cells (MSC), and evaluate the mechanism of action involved. Cell viability was assessed 72 hours post-treatment using MTS assay. The cellular uptake of both compounds was measured by ICP-MS. Their effect on DNA fragmentation was then tested using Comet assay. The type of cell death was assessed by flow cytometry. Evaluation of apoptotic proteins’ expression was performed using western blots. Results showed that both complexes significantly reduced cancer cell viability and exhibited 7 to 20-fold higher cytotoxicity compared to cisplatin. Pt(IV) showed remarkable selectivity towards different cancer cells (17-22 fold) compared with mesenchymal stem cells. While both complexes were actively transported into the cells, Pt(II) showed a faster and higher uptake compared to its platinum IV analogue. Pt(IV) but not Pt(II) treatment caused significant DNA fragmentation in A549 cells. Western blot analysis demonstrated an upregulation of Bax/Bcl-2 ratio and cytochrome c, downregulation of procaspases 3 and 9 and cleavage of Parp for both Pt(II) and Pt(IV), which indicates that apoptosis was induced through the intrinsic pathway. No effect on procaspase 8 was observed, eliminating the involvement of the extrinsic apoptotic pathway. Flow cytometry analysis confirmed the apoptotic cell death caused by both platinum complexes. In conclusion, Pt(II) and Pt(IV) may be considered as promising anti-cancer drugs with Pt(IV) being more selective to cancer cells, which might provide a robust alternative for currently approved anticancer platinum medications.